Corporate Governance and Performance of Malaysian Public Listed Companies - Sahar Effendi, Daud (2012)
The issuance of the amended Malaysian Code on Corporate Governance (MCCG) in 2007 clearly shows that continuous efforts have been done by the regulators and policy makers to enhance good governance practices in Malaysia. Based on the MCCG, this study investigates the extent of the corporate governance practices and examines the relationship between corporate governance practices and the performance among Malaysian listed companies. All listed companies for the financial year of 2009 which are rated using the Governance and Transparency Index 2009 issued by the Minority Shareholder Watchdog Group are accordingly scored in the present study. In addition, agency theory is used to explain the corporate governance practices and the firms’ behaviour which is based on the agent’s action, and the objective of maximising the shareholders’ wealth. The result indicates that the level of the corporate governance practices is low for the Board of Directors’ Structure, very low for Directors’ Remuneration and moderate for Accountability and Audit, and Communication with Shareholders. Using EPS and ROE as the performance measurement, this study suggests that the Board Size, CEO-Chairman Role Separation, Disclosure of Senior Independent Director, Mix Use of Executive Directors’ Remuneration and Disclosure of Top 5 Executives’ Remuneration have positive relationship with the firm’s performance. Although the Corporate Governance Blueprint 2011 recognises the importance of CEO-Chairman role separation and the establishment of effective and transparent disclosure, emphasis should also be given to the board size as well as the usage of various avenues of remunerating Executive Directors as the study suggests. Policy makers and regulators should consider encouraging listed companies to have the most optimal number of board members and to use a mixture of methods in remunerating Executive Directors for future improvements to the MCCG.